Hydrogen-assisted microcrack formation in bearing steels under rolling contact fatigue. (May 2020) - Liang, X.Z.; Zhao, G.-H.; Owens, J.; Gong, P.; Rainforth, W.M.; Rivera-Díaz-del-Castillo, P.E.J.
Highlights: H induces voids and cracks at grain boundaries during rolling contact fatigue. Mixed H embrittlement mechanism: localised plasticity and intergranular debonding. Quantitative proof of increased void and crack populations upon H ingress. Abstract: A ball-on-rod RCF tester was employed to investigate the failure mechanisms of hydrogen-rich rolling components. The formation of defects, voids and surface cracks is significantly facilitated in hydrogen-rich bearing steels. In samples with RCF cycles of 1.6 × 10 7, the void density in hydrogen-rich samples is about three times that of hydrogen-free samples, whilst their crack length density four times that of hydrogen-free samples. This is due to a higher stress intensity factor around inclusions which is altered by hydrogen. Further characterisation confirms that grain boundaries are preferential sites for void formation and crack propagation.